Lord Sunday - Nix, Garth (Nix, Garth. Keys to the kingdom, 2010)
As Arthur Penhaligon seeks to find the seventh key, complete his quest to save the Kingdom to which he is heir, and learn his true identity, he discovers that he has a greater purpose than he could have imagined.